The South–South Remittance Corridor between Argentina and Bolivia - Matteo Mandrile (United Nations, 2014)
South–South remittance corridors still remain a largely unexplored research area, despite the fact that for a few years already, international organizations, such as the International Organization for Migration and the World Bank, have been highlighting the importance of South–South migration and remittance flows. In South America, the Argentina–Bolivia corridor is the third most relevant South–South corridor in terms of annual volumes, after Venezuela–Colombia and Argentina–Paraguay. This publication provides a diagnostic report on the access to and use of remittance services by Bolivian migrants in Argentina, showing the main obstacles and challenges faced to achieve a productive use of remittances. The study examines the legal and regulatory frameworks of remittance-related transactions, together with the sending process from Argentina to Bolivia, with its chain of intermediation and different money transfer schemes. It provides key recommendations for public policies and actions aimed at maximizing the positive impact of remittances in terms of local development, focusing on two intervention pillars: financial education and transparency of the remittance services market.